Seroprevalence of Rift Valley fever and lumpy skin disease in African buffalo (Syncerus caffer) in the Kruger National and Hluhluwe-iMfolozi Parks, South Africa - Venter, Estelle Hildegard (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2012.